Lightweight high-entropy alloy nano composite material as well as preparation method and application thereof
By introducing whiskers and two-dimensional sheet nanomaterials into lightweight high-entropy alloys to form nanocomposites, the problem of insufficient toughness in traditional lightweight high-entropy alloys under extreme conditions is solved, and significant improvement in mechanical properties and stability is achieved.
Patent Information
- Application Number
- CN202411996871.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional lightweight high-entropy alloys have problems of insufficient toughness and brittleness under extreme conditions such as high temperature and high pressure, and they need to improve their mechanical properties and toughness.
By introducing whiskers and two-dimensional sheet nanomaterials into the lightweight high-entropy alloy matrix, nanocomposites are formed, and the grain boundary strengthening, lattice distortion and phase separation effects of the material are enhanced by utilizing the high strength of the whiskers and the high hardness and thermal conductivity of the two-dimensional sheet nanomaterials.
The strength, toughness, plasticity, high temperature resistance and corrosion resistance of lightweight high entropy alloys are significantly improved, so that they can show better mechanical properties and stability under extreme conditions.
Smart Images

Figure CN119876792A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lightweight high entropy alloy materials, and in particular to a lightweight high entropy alloy nanocomposite material and a preparation method and application thereof. Background Art
[0002] Lightweight high entropy alloy is a new type of alloy material with low density and high entropy alloy properties. It has flexible and adjustable diversified structure and potential properties. Due to its unique microstructure and excellent performance, lightweight high entropy alloys have shown great application potential in many fields. However, traditional lightweight high entropy alloys still have problems such as insufficient toughness and brittleness under certain extreme conditions (such as high temperature and high pressure). Therefore, how to further improve the mechanical properties of lightweight high entropy alloys, especially toughness and high temperature stability, has become a hot topic in current research. Summary of the invention
[0003] In view of the above analysis, the present invention aims to provide a lightweight high-entropy alloy nanocomposite material and a preparation method and application thereof, so as to solve at least one of the following existing problems: improving the mechanical properties of lightweight high-entropy alloys and improving the toughness of lightweight high-entropy alloys.
[0004] The purpose of the present invention is mainly achieved through the following technical solutions:
[0005] In the first aspect, the present invention provides a lightweight high-entropy alloy nanocomposite material, comprising a lightweight high-entropy alloy matrix, whiskers and flaky nanomaterials. Based on the total weight of the composite material, the mass percentage of the whiskers is 0.01wt.% to 5.00wt.%; the mass percentage of the flaky nanomaterials is 0.01wt.% to 10.00wt.%.
[0006] Preferably, the material of the whiskers includes at least one of MgO, ZnO, Al2O3, BeO, SnO2, MnO2, NiO, Y2O3, CdO, NbO, TiO2, In2O3, GeO2, Cr2O3, TiB2, ZrB2, TaB2, CrB, NbB2, Si3N4, BN, AlN, TiN, SiC, Ni, Fe, Cu, Si, Ag, Ti, mullite, and calcium sulfate.
[0007] Preferably, the material of the flaky nanomaterial includes at least one of graphene, h-BN, c-BN, MoS2, MoSe2, WS2, hydrotalcite, CuO, WO3, and ZrMo2O8.
[0008] Preferably, the whisker has a length of 1 to 70 μm and a diameter of 0.001 to 0.200 μm.
[0009] Preferably, the particle size of the sheet-like nanomaterial is 10 to 200 nm, and the thickness is 1 to 100 nm.
[0010] Preferably, the lightweight high-entropy alloy matrix includes metal components, and the metal components include at least five of Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Hf, Ta, and W.
[0011] Preferably, the density of the lightweight high entropy alloy is not greater than 7.87 g / cm 3 , preferably 3.5-7.87 g / cm 3 .
[0012] Preferably, the metal component includes a first metal component, a second metal component, a third metal component, a fourth metal component, and a fifth metal component that are different from each other; calculated based on the total atomic percentage of the lightweight high entropy alloy matrix as 100%, the atomic percentages of the first metal component, the second metal component, the third metal component, the fourth metal component, and the fifth metal component are the same or different, and are each independently 5 to 35 at.%.
[0013] In a second aspect, the present invention provides a method for preparing the lightweight high entropy alloy nanocomposite material, comprising:
[0014] A mixture including metal component powders is obtained, subjected to a first vacuum arc melting, and then whiskers and flaky nanomaterials are added and subjected to a second vacuum arc melting to obtain the lightweight high entropy alloy nanocomposite material.
[0015] Preferably, the temperature of the first vacuum arc melting is 2500-3000° C., and / or the pressure of the first vacuum arc melting is 0.05-0.08 Pa.
[0016] Preferably, the temperature of the second vacuum arc melting is 1500-1700° C., and / or the pressure of the second vacuum arc melting is 0.05-0.08 Pa.
[0017] In a third aspect, the present invention provides an application of the lightweight high entropy alloy nanocomposite material, wherein the lightweight high entropy alloy nanocomposite material is used for parts in the fields of aerospace, medicine, energy, military and transportation.
[0018] Beneficial effects:
[0019] The light high entropy alloy nanocomposite material provided by the present invention, wherein two-dimensional flaky nanoparticles and whisker nanoparticles are added to the light high entropy alloy as reinforcing and toughening materials, has an enhancing and optimizing effect on the grain boundary strengthening, lattice distortion and metastable effect, phase separation effect, and compatibility of each metal component element of the light high entropy alloy, and also has the effect of refining the grains, which can not only improve the strength, toughness, plasticity, and high temperature resistance of the light high entropy alloy, but also help to improve the corrosion resistance and wear resistance of the light high entropy alloy. The nanocomposite material prepared by combining two-dimensional flaky nanomaterials and nano whiskers with light high entropy alloys further improves the performance of light high entropy alloy materials, and can be widely used in aerospace, medicine, energy, transportation and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 These are SEM images of the mullite whisker and the two-dimensional sheet material c-BN of Example 3 provided by the present invention, wherein (a) is the SEM image of the mullite whisker, and (b) is the SEM image of the two-dimensional sheet material c-BN.
[0021] Figure 2 These are SEM images of the materials of Comparative Example 3 and Example 3 provided by the present invention, wherein (a) is the SEM image of Comparative Example 3, and (b) is the SEM image of Example 3.
[0022] Figure 3 These are stress-strain curves of the materials of Example 3 and Comparative Example 3 provided by the present invention.
[0023] Figure 4 XRD curves of the materials of Example 3 and Comparative Example 3 provided by the present invention. DETAILED DESCRIPTION
[0024] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.
[0025] The introduction of whiskers and two-dimensional sheet-like nanomaterials as reinforcing phases into lightweight high-entropy alloy matrices is expected to significantly improve the comprehensive performance of composite materials. Among them, whiskers have excellent properties such as high strength, high modulus, and low thermal expansion coefficient, which can effectively improve the strength and toughness of the matrix material. Two-dimensional sheet-like nanomaterials have become an ideal choice for enhancing the hardness and high temperature resistance of metal-based composites due to their high hardness, high thermal conductivity, and good chemical stability.
[0026] The present invention relates to a whisker and two-dimensional flaky nanomaterial toughened high entropy alloy nanocomposite material and a preparation method thereof. The composite material introduces whiskers and two-dimensional flaky nanoparticles into a high entropy alloy matrix, so that the alloy forms grain boundary strengthening and grain boundary pinning effects, thereby significantly improving the toughness, hardness and high temperature stability of the material. The specific preparation method includes the steps of preparing high entropy alloy powder, adding whiskers and two-dimensional flaky nanoparticles, ball milling of the mixed powder, pre-pressing and vacuum arc melting. The composite material has broad application prospects in the fields of aerospace, nuclear energy, high temperature structural materials, etc.
[0027] Hereinafter, the present invention will be described in detail.
[0028] In a first aspect, the present invention provides a lightweight high entropy alloy nanocomposite material, comprising a lightweight high entropy alloy matrix, whiskers and a two-dimensional sheet-like nanomaterial, based on the total weight of the composite material.
[0029] The mass percentage of the whiskers is 0.01wt.% to 5.00wt.%, for example, 0.01wt.%, 0.05wt.%, 0.1wt.%, 0.5wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, 5wt.%, etc.; preferably 0.9wt.% to 4.00wt.%;
[0030] The mass percentage of the two-dimensional flaky nanomaterial is 0.01wt.% to 10.00wt.%, for example, 0.01wt.%, 0.05wt.%, 0.1wt.%, 0.5wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, 5wt.%, 5.5wt.%, 6wt.%, 6.5wt.%, 7wt.%, 7.5wt.%, 8wt.%, 8.5wt.%, 9wt.%, 9.5wt.%, 10wt.%, etc., preferably 7wt.% to 9wt.%.
[0031] The light high entropy alloy nanocomposite material of the present invention, wherein two-dimensional flaky nanoparticles and whisker nanoparticles are added as reinforcing and toughening materials to the light high entropy alloy, has an enhancing and optimizing effect on the grain boundary strengthening, lattice distortion and metastable effect, phase separation effect, and compatibility of each metal component element of the light high entropy alloy, and can improve the strength, toughness, plasticity, high temperature resistance, corrosion resistance, wear resistance and other properties of the light high entropy alloy. The nanocomposite material prepared by combining two-dimensional flaky nanomaterials and nano whiskers with light high entropy alloys further improves the performance of light high entropy alloy materials, and can be widely used in aerospace, medicine, energy, military and transportation fields.
[0032] In some specific embodiments of the present invention, the type of the whiskers is at least one of MgO, ZnO, Al2O3, BeO, SnO2, MnO2, NiO, Y2O3, CdO, NbO, TiO2, In2O3, GeO2, Cr2O3, TiB2, ZrB2, TaB2, CrB, NbB2, Si3N4, BN, AlN, TiN, SiC, Ni, Fe, Cu, Si, Ag, Ti, mullite whiskers (3Al2O3·2SiO2), and high-performance calcium sulfate whiskers (CaSO4), and is preferably at least one of TiO2, SiC, mullite whiskers, ZrB2, and AlN.
[0033] In some specific embodiments of the present invention, the whiskers have a length of 1-70 μm and a diameter of 0.001-0.200 μm.
[0034] In some specific embodiments of the present invention, the two-dimensional sheet-like nanomaterial is at least one of graphene, h-BN, c-BN, MoS2, MoSe2, WS2, hydrotalcite, CuO, WO3, and ZrMo2O8, and is preferably at least one of graphene, h-BN, c-BN, MoS2, and ZrMo2O8.
[0035] In some specific embodiments of the present invention, the two-dimensional sheet-like nanomaterial is a nanoparticle with a particle size of 10 to 200 nm and a thickness of 1 to 100 nm, and the thickness of the two-dimensional sheet-like nanomaterial is much smaller than the particle size.
[0036] In some specific embodiments of the present invention, the lightweight high entropy alloy matrix includes metal components, and the metal components are selected from at least five of Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Hf, Ta, and W.
[0037] In some specific embodiments of the present invention, the metal components include a first metal component x1, a second metal component x2, a third metal component x3, a fourth metal component x4, and a fifth metal component x5; calculated based on the atomic percentage of the lightweight high entropy alloy matrix, the atomic percentages of x1, x2, x3, x4, and x5 are the same or different, and are each independently 5 to 35 at.%, for example, 5 at.%, 8 at.%, 11 at.%, 14 at.%, 17 at.%, 20 at.%, 23 at.%, 26 at.%, 29 at.%, 32 at.%, 35 at.%, etc., and the total atomic percentage is calculated as 100%.
[0038] In some specific embodiments of the present invention, the lightweight high entropy alloy refers to an alloy density not greater than the iron density of 7.87 g / cm 3, preferably 3.5-7.87 g / cm 3 , and alloy materials with configurational entropy greater than 1.5R under random atomic occupation.
[0039] In the present invention, the two-dimensional sheet-like nanomaterials and nano whiskers have the following advantages in strengthening and toughening lightweight high entropy alloys:
[0040] (1) Whiskers are a type of fibrous single-crystal material with high strength and high modulus. Their diameter is usually in the nanometer to micrometer range. Their internal atomic arrangement is highly ordered and has few defects. This high purity and single-crystal structure give nanowhiskers a strength close to the theoretical value of the interatomic force of the material. Adding whiskers to lightweight high-entropy alloy nanocomposites can serve as the core of heterogeneous nucleation, promoting the nucleation and grain refinement of high-entropy metals during solidification. Since the atomic size of the elements contained in whiskers is quite different from that of alloy atoms, severe lattice distortion is formed. At the same time, the active elements contained in whiskers are added to the grain boundaries, forming grain boundary strengthening and grain boundary pinning effects, which can effectively hinder dislocation movement and significantly improve the strength and toughness of the material.
[0041] (2) Nanowhiskers usually have good chemical stability and thermal stability due to their special structure and composition. Adding nanowhiskers to lightweight high-entropy alloy materials can increase the melting point of lightweight high-entropy alloy materials and inhibit the grain growth of high-entropy metals at high temperatures, thereby maintaining the excellent mechanical properties and thermal stability of lightweight high-entropy alloys, making them have better stability and thermal shock resistance at high temperatures.
[0042] (3) Nanowhiskers can form a dense protective layer on the surface of lightweight high-entropy alloys, improve the electrochemical properties of lightweight high-entropy alloys, make them more stable and durable in corrosive environments, and reduce the erosion of corrosive media on the materials to a certain extent.
[0043] (4) Two-dimensional sheet nanomaterials Since the movement of electrons is restricted in two dimensions, the atoms of the nanomaterials are connected by covalent bonds, stacked and extended laterally, so that they have lateral dimensions ranging from hundreds of nanometers to tens of microns or even larger, but the thickness is only a single or a few atomic layers. This gives them an ultra-high specific surface area and extremely small size effect and quantum size effect. Adding two-dimensional sheet nanomaterials to lightweight high-entropy alloys can form an effective crack barrier layer inside them to prevent the expansion of cracks, thereby improving the toughness of lightweight high-entropy alloy materials. Two-dimensional nanomaterials can also act as stress absorbers to absorb and disperse stress in composite materials, further enhancing the toughness of the material.
[0044] (5) Two-dimensional sheet nanomaterials have good electron transport properties. Since the movement of electrons is restricted by the two-dimensional plane, two-dimensional sheet nanomaterials can serve as good channels for electron transport and can effectively improve the conductivity of lightweight high-entropy alloys.
[0045] (6) Two-dimensional sheet nanomaterials and nanowhisker materials exhibit the characteristics of low addition amount and high efficiency, that is, only a small amount of nanowhiskers and two-dimensional nanomaterials are needed to bring about significant performance enhancement, thus having excellent economic efficiency.
[0046] (7) High temperature resistance. The high temperature resistance of lightweight high entropy alloy nanocomposites toughened by two-dimensional flaky nanomaterials and nanowhisker materials is mainly due to the multi-element structure, excellent thermal stability and corrosion resistance of lightweight high entropy alloys, as well as the toughening effect of two-dimensional flaky nanomaterials and nanowhisker materials. Lightweight high-entropy alloys easily form FCC or BCC dendritic crystal structures with low free enthalpy. After the two-dimensional flaky nanomaterials and nanowhiskers are added, a synergistic effect is produced. The two-dimensional flaky nanomaterials have interlayer spacing, and the nanowhiskers are intercalated into the middle of the two-dimensional flaky nanomaterials to form a multi-level reinforcement phase, which makes it easy for the lightweight high-entropy alloy matrix to generate a second phase in the alloy structure, resulting in the formation of amorphous, microcrystalline and nanophase structures at the grain boundaries, aggravating the lattice distortion effect of the lightweight high-entropy alloy, making the diffusion rate of atoms in the lightweight high-entropy alloy slower. At the same time, the addition of two-dimensional flaky nanomaterials and nanowhisker materials causes the alloy to produce a second phase strengthening, which hinders the movement of dislocations under high-temperature compression, further improving the mechanical properties and corrosion resistance of the alloy. At the same time, this corrosion resistance makes the alloy not easily oxidized or corroded at high temperatures, thereby also improving the high-temperature performance of the alloy.
[0047] In a second aspect, the present invention provides a method for preparing a lightweight high entropy alloy nanocomposite material, comprising the following steps:
[0048] Step 1: Evenly mix the powders of the metal components of the lightweight high entropy alloy matrix to obtain a mixed powder;
[0049] Step 2: Performing the first vacuum arc melting to obtain a high entropy alloy matrix;
[0050] Step 3: Add whiskers and two-dimensional flaky nanomaterials and perform a second vacuum arc melting to obtain a lightweight high-entropy alloy nanocomposite material.
[0051] The preparation method provided by the present invention uses a vacuum arc melting method to prepare a lightweight high-entropy alloy nanocomposite material containing two-dimensional flaky nanomaterials and nanowhiskers, which has uniform composition and more stable performance. Vacuum arc melting is performed in a vacuum environment to avoid oxidation of the alloy. At the same time, the high-temperature melting environment helps to remove impurities and gases in the alloy, accelerate the diffusion and reaction of elements in the alloy, and make the alloy composition more uniform and stable.
[0052] It should be noted that due to the high melting point of some components of the high entropy alloy matrix, the two-dimensional flaky nanomaterials and nanowhiskers cannot be directly melted together with the powder, and must be melted twice. First, the high entropy alloy matrix is melted into an alloy block and then the two-dimensional flaky nanomaterials and nanowhiskers are added for secondary melting.
[0053] In some specific embodiments of the present invention, in step 2, the temperature for melting the high entropy alloy matrix in the first vacuum arc melting is 2500-3000° C. and the pressure is 0.05-0.08 Pa.
[0054] In some specific embodiments of the present invention, in step 3, the temperature for melting the high entropy alloy nanocomposite material in the second vacuum arc melting is 1500-1700° C. and the pressure is 0.05-0.08 Pa.
[0055] It should be noted that the existing technology mostly uses plasma sintering process, which can cause the temperature of the metal material to not reach its melting point, and the various elements in the molten metal cannot react completely, thus affecting the density, organizational structure and mechanical properties of the alloy. Vacuum arc furnace melting melts metal materials under high temperature conditions, which is conducive to their full and uniform fusion, avoiding the contamination of the molten metal by the refractory lining, thereby ensuring the purity of the molten metal; it can also process materials of various shapes and sizes, including blocks, rods, etc., with greater flexibility.
[0056] In some specific embodiments of the present invention, step 1 comprises the following steps:
[0057] Step 1a: preparing high entropy alloy powder;
[0058] Step 1b: ball milling;
[0059] Step 1c: Pre-pressing.
[0060] In some specific embodiments of the present invention, in step 1a, high entropy alloy powder is prepared by ball milling. The specific steps may be: after the metal powders are evenly mixed, ball milling is performed to obtain high entropy alloy powder. Preferably, the ball milling time is controlled to be 10 hours or more until the powder particle size reaches the micro-nano level. More preferably, the ball milling time can be 10 to 70 hours.
[0061] In some specific embodiments of the present invention, the specific steps of step 1a may be: metal powder with a purity of more than 99.5% is selected as the raw material, and the mesh size of the raw material is 350-500 mesh, and the raw material is subjected to mechanical alloying treatment: the above metal powders are mixed, and after all the metal powders are mixed, they are placed in a planetary ball mill for mechanical alloying treatment. During the ball milling process, high-purity argon gas is introduced as a protective gas to prevent powder oxidation.
[0062] In some specific embodiments of the present invention, in step 1b, the high entropy alloy powder is ball-milled to further refine the uniform distribution of each component in the powder particle matrix. Preferably, the ball-milling time is 10 to 20 hours.
[0063] In some specific embodiments of the present invention, in step 1c, the pre-pressing pressure is 3-10 MPa.
[0064] In a specific embodiment of the present invention, the specific steps of the method for preparing the lightweight high entropy alloy nanocomposite material are as follows:
[0065] Step 1a: Preparation of high entropy alloy powder: The raw material is a metal powder with a purity of more than 99.5%, and the mesh size of the raw material is 350-500 mesh. Mechanical alloying treatment of raw materials: Mix the above metal powders. After all the metal powders are mixed, they are placed in a planetary ball mill for mechanical alloying treatment. During the ball milling process, high-purity argon is introduced as a protective gas to prevent powder oxidation. The ball milling time is controlled to be 10 hours or more until the powder particle size reaches the micro-nano level.
[0066] Step 1b: Ball milling: The mixed powder is put into a planetary ball mill again for ball milling, and the ball milling time is controlled within 10 to 20 hours.
[0067] Step 1c: Pre-pressing: The mixed powder after ball milling is pre-pressed at 3-10 MPa to obtain a pre-pressed green body.
[0068] Step 2: Melting high entropy alloy block: Place the pre-pressed green body into a vacuum arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing for multiple times (preferably 2-5 times). Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to above 0.05Pa (preferably 0.05-0.08Pa) to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700°C, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process, and each stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted for multiple times (preferably 2-4 times) to ensure uniform melting. After melting for about 0.5h, a high entropy alloy block is obtained.
[0069] Step 3: Melting high entropy alloy nanocomposite materials: Place the high entropy alloy block melted in the previous step, as well as the whiskers and two-dimensional sheet-like nanomaterials into a vacuum arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing for multiple times (preferably 2-5 times). Then evacuate the vacuum to 3.0×10 -3Pa, and fill with argon to above 0.05Pa (preferably 0.05-0.08Pa) to form an inert atmosphere in the furnace. Maintain the melting temperature in the furnace at 1500-1700°C, and perform melting in an atmosphere of inert gas argon. During the melting process, the magnetic stirring function needs to be turned on, and each stirring takes 2-10s. Each sample needs to be repeatedly turned over and melted for multiple times (preferably 2-4 times) to ensure uniform melting. After melting for about 0.5h, a high-strength and toughened high-entropy alloy nanocomposite material is obtained.
[0070] In a third aspect, the present invention provides an application of a lightweight high entropy alloy nanocomposite material for use in the manufacture of parts in the fields of aerospace, medicine, energy, and transportation.
[0071] The preferred embodiments of the present invention are described in detail below to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0072] In the present invention, unless otherwise specified, all reagents used are commercially available products, including:
[0073] In the following examples, the length of each type of whisker is 1-70 μm and the diameter is 0.001-0.200 μm.
[0074] In the following examples, the particle size of various types of two-dimensional sheet-like nanomaterials is 10 to 200 nm and the thickness is 1 to 100 nm.
[0075] Comparative Example 1
[0076] Preparation of a lightweight high entropy alloy material:
[0077] First, through the batching, five pure metal powders of Al, Nb, Cu, Cr, and Fe with a purity of 99.95% were selected as raw materials. 0.5 20 g of NbTi3VZr was weighed and mixed, and then the metal powders were put into a planetary ball mill for 40 h until the powders were alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent the powders from oxidation.
[0078] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0079] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0080] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, Al 0.5 NbTi3VZr lightweight high entropy alloy material.
[0081] After research and testing, Al 0.5 The yield strength of the NbTi3VZr lightweight high entropy alloy at room temperature is 1200MPa, and the elongation is >50%. The yield strength at 800°C is 236MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0082] Example 1
[0083] Preparation of a high-strength, toughened, lightweight high-entropy alloy material:
[0084] First, through the batching, five pure metal powders of Al, Nb, Cu, Cr, and Fe with a purity of 99.95% were selected as raw materials. 0.5 20 g of NbTi3VZr was weighed and mixed, and then the metal powders were put into a planetary ball mill for 40 h until the powders were alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent the powders from oxidation.
[0085] 0.2g TiO2 and 2g graphene were used as reinforcing agents to mix the whiskers and the two-dimensional sheet-like nanomaterials evenly.
[0086] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0087] The ball-milled metal mixed powder is pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0088] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, Al 0.5 NbTi3VZr lightweight high entropy alloy block.
[0089] The high entropy alloy block melted in the previous step, 0.2g TiO2 and 2g graphene are placed in a vacuum arc melting furnace at a melting temperature of 1500-1700℃. The above steps are repeated for about 0.5h to obtain graphene / TiO2 / Al 0.5 NbTi3VZr high-strength, toughened, lightweight high-entropy alloy nanocomposites.
[0090] Graphene / TiO2 / Al 0.5 The yield strength of the NbTi3VZr lightweight high entropy alloy nanocomposite material at room temperature is 1365MPa, and the elongation is >50%. The yield strength at 800°C is 354MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0091] Comparative Example 2
[0092] Preparation of a lightweight high entropy alloy material:
[0093] First, five pure metal powders of Al, Nb, Cu, Cr and Fe with a purity of 99.95% were selected as raw materials. 0.25 20 g of ingredients were weighed and mixed, and then the metal powders were placed in a planetary ball mill for 40 hours until the powders were alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent oxidation of the powders.
[0094] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0095] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0096] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, AlNbTiVZr is obtained. 0.25 Lightweight high entropy alloy materials.
[0097] After research and testing, AlNbTiVZr 0.25The yield strength of the light high entropy alloy at room temperature is 1360 MPa and the elongation is 9.5%. The yield strength of the alloy at 800°C is 855 MPa and the elongation is >50%. The specific results are listed in Table 1.
[0098] Example 2
[0099] Preparation of a high-strength, toughened, lightweight high-entropy alloy material:
[0100] First, through the batching, five kinds of pure metal powders of Al, Nb, Cu, Cr, and Fe with a purity of 99.95% or more are selected as raw materials. 0.25 20 g of ingredients were weighed and mixed, and then the metal powders were placed in a planetary ball mill for 40 hours until the powders were alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent oxidation of the powders.
[0101] 0.2 g of SiC whiskers and 1.6 g of h-BN were used as reinforcing agents, and the whiskers and the two-dimensional flaky nanomaterials were mixed evenly.
[0102] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0103] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0104] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, AlNbTiVZr is obtained. 0.25 Lightweight high entropy alloy bulk materials.
[0105] The high entropy alloy block melted in the previous step, 0.2g of SiC whiskers and 1.6g of h-BN were placed in a vacuum arc melting furnace at a melting temperature of 1500-1700℃. The above steps were repeated for about 0.5h to obtain c-BN / SiC / AlNbTiVZr 0.25 High-strength, toughened, lightweight high-entropy alloy nanocomposites.
[0106] After research and testing, c-BN / SiC / AlNbTiVZr 0.25 The yield strength of the lightweight high entropy alloy nanocomposite at room temperature is 1486 MPa, and the elongation is 13.6%. The yield strength of the alloy at 800°C is 989 MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0107] Comparative Example 3
[0108] Preparation of a lightweight high entropy alloy material:
[0109] First, through the batching, five kinds of pure metal powders of Al, Nb, Ti, V and Zr with a purity of 99.95% or more are selected as raw materials, according to AlNbTi2V 1.5 Zr was weighed and mixed with 20 g of the metal powder, and then put into a planetary ball mill for 40 hours until the powder was alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent the powder from oxidation.
[0110] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0111] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0112] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, AlNbTi2V 1.5 Zr lightweight high entropy alloy material.
[0113] After research and testing, AlNbTi2V 1.5 The yield strength of the Zr lightweight high entropy alloy at room temperature is ~1952MPa, and the elongation is 10.7%. The yield strength of the alloy at 800°C is ~563MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0114] Example 3
[0115] Preparation of a high-strength, toughened, lightweight high-entropy alloy material:
[0116] First, through the batching, five kinds of pure metal powders of Al, Nb, Ti, V and Zr with a purity of 99.95% or more are selected as raw materials, according to AlNbTi2V 1.5 Zr was weighed and mixed with 20 g of the metal powder, and then put into a planetary ball mill for 40 hours until the powder was alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent the powder from oxidation.
[0117] 0.4 g of mullite whiskers and 1.6 g of c-BN were used as reinforcing agents, and the whiskers and the two-dimensional flaky nanomaterials were mixed evenly.
[0118] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0119] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0120] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, AlNbTi2V 1.5 Zr lightweight high entropy alloy.
[0121] The light high entropy alloy block melted in the previous step, 0.4g of mullite whiskers and 1.6g of c-BN were placed in a vacuum arc melting furnace at a melting temperature of 1500-1700℃. The above steps were repeated for about 0.5h to obtain c-BN / mullite whiskers / AlNbTi2V 1.5 Zr high-strength toughened lightweight high-entropy alloy nanocomposites.
[0122] After research and testing, c-BN / Mullite Whiskers / AlNbTi2V 1.5 The yield strength of the Zr lightweight high entropy alloy nanocomposite at room temperature is ~2089MPa, and the elongation is 17.8%. The yield strength of the alloy at 800℃ is ~649MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0123] Comparative Example 4
[0124] Preparation of a lightweight high entropy alloy material:
[0125] First, through the batching, five or more pure metal powders of Al, Hf, Nb, Ti, and Zr with a purity of 99.95% are selected as raw materials. According to CoFeNiVAl, 20g of the ingredients are weighed and mixed. After all the metal powders are mixed, they are put into a planetary ball mill for ball milling for 40 hours until the powder is alloyed. During the ball milling process, high-purity argon gas is introduced as a protective gas to prevent the powder from oxidation.
[0126] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0127] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0128] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, CoFeNiVAl lightweight high entropy alloy material is obtained.
[0129] The yield strength of the CoFeNiVAl lightweight high entropy alloy at room temperature is ~1150MPa, and the elongation is 28%. The yield strength of the alloy at 800°C is ~194MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0130] Example 4
[0131] Preparation of a high-strength, toughened, lightweight high-entropy alloy material:
[0132] First, through the batching, five or more pure metal powders of Al, Hf, Nb, Ti, and Zr with a purity of 99.95% are selected as raw materials. According to CoFeNiVAl, 20g of the ingredients are weighed and mixed. After all the metal powders are mixed, they are put into a planetary ball mill for ball milling for 40 hours until the powder is alloyed. During the ball milling process, high-purity argon gas is introduced as a protective gas to prevent the powder from oxidation.
[0133] 0.4 g of ZrB2 whiskers and 2 g of MoS2 were used as reinforcing agents, and the whiskers and the two-dimensional flaky nanomaterials were mixed evenly.
[0134] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0135] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0136] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace chamber. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, CoFeNiVAl lightweight high entropy alloy material is obtained.
[0137] The light high entropy alloy block melted in the previous step, 0.4g of ZrB2 whiskers and 2g of MoS2 are placed in a vacuum arc melting furnace at a melting temperature of 1500-1700°C. The above steps are repeated. After melting for about 0.5h, a MoS2 / ZrB2 / CoFeNiVAl high-strength and toughened light high entropy alloy nanocomposite material is obtained.
[0138] The yield strength of the MoS2 / ZrB2 / CoFeNiVAl lightweight high entropy alloy nanocomposite material at room temperature is ~1235MPa, and the elongation is 33.6%. The yield strength of the alloy at 800°C is ~287MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0139] Comparative Example 5
[0140] Preparation of a lightweight high entropy alloy material:
[0141] First, through the batching, five or more pure metal powders of Co, Fe, Ni, V, and Al with a purity of 99.95% are selected as raw materials. 0.75 20 g of ingredients were weighed and mixed, and then the metal powders were placed in a planetary ball mill for 40 hours until the powders were alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent oxidation of the powders.
[0142] The metal component mixed powder was put into the planetary ball mill again for ball milling for 10 hours to further refine the powder particles and evenly distribute them.
[0143] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body.
[0144] Add the pre-pressed green body into the cleaned arc melting furnace, close the furnace cover, turn on the power supply and cooling circulation system. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum evacuation and gas washing 3 times. Then evacuate the vacuum to 3.0×10 -3 Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, CoFeNiVAl 0.75 Lightweight high entropy alloy materials.
[0145] After research and testing, CoFeNiVAl 0.75 The yield strength of the lightweight high entropy alloy at room temperature is ~1300MPa, and the elongation is 32%. The yield strength of the alloy at 800°C is ~233MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0146] Example 5
[0147] Preparation of a high-strength, toughened, lightweight high-entropy alloy material.
[0148] First, through the batching, five or more pure metal powders of Co, Fe, Ni, V, and Al with a purity of 99.95% are selected as raw materials. 0.75 20 g of ingredients were weighed and mixed, and then the metal powders were placed in a planetary ball mill for 40 hours until the powders were alloyed. During the ball milling process, high-purity argon was introduced as a protective gas to prevent oxidation of the powders.
[0149] 0.4 g of AlN whiskers and 2 g of ZrMo2O8 were used as reinforcing agents, and the whiskers and the two-dimensional flaky nanomaterials were mixed evenly.
[0150] The mixed powder was again placed in a planetary ball mill for ball milling for 10 h to further refine the powder particles and evenly distribute them.
[0151] The mixed powder after ball milling was pre-pressed at a pressure of 5 MPa to obtain a pre-pressed green body. The pre-pressed green body was added to a clean arc melting furnace, the furnace cover was closed, and the power supply and cooling circulation system were turned on. The vacuum system was turned on, the vacuum degree was evacuated to below 20 Pa, and argon gas was introduced for gas washing. The vacuum was evacuated and gas washing was repeated 3 times. Then the vacuum degree was evacuated to 3.0×10 - 3Pa, and fill with argon to 0.05Pa to form an inert atmosphere in the furnace. Keep the melting temperature in the furnace at 2700℃, and melt in an atmosphere of inert gas argon. The magnetic stirring function needs to be turned on during the melting process. Each magnetic stirring lasts for 2-10s. Each sample needs to be repeatedly turned over and melted 6 times to ensure uniform melting. After melting for about 0.5h, CoFeNiVAl 0.75 Lightweight high entropy alloy materials.
[0152] The light high entropy alloy block melted in the previous step, 0.4g of AlN whiskers and 2g of ZrMo2O8 were placed in a vacuum arc melting furnace at a melting temperature of 1500-1700℃. The above steps were repeated for about 0.5h to obtain ZrMo2O8 / AlN / CoFeNiVAl 0.75 High-strength, toughened, lightweight high-entropy alloy nanocomposites.
[0153] After research and testing, ZrMo2O8 / AlN / CoFeNiVAl 0.75 The yield strength of the lightweight high entropy alloy nanocomposite material at room temperature is ~1462MPa, and the elongation is 37.3%. The yield strength of the alloy at 800°C is ~328MPa, and the elongation is >50%. The specific results are listed in Table 1.
[0154] Example 6
[0155] This embodiment is basically the same as the embodiment 1, except that the type of the two-dimensional sheet-like nanomaterial is WS2, and the mass percentage of WS2 is 9%.
[0156] Example 7
[0157] This embodiment is substantially the same as the embodiment 1, except that the type of whiskers is alumina whiskers and the mass percentage of mullite whiskers is 0.9%.
[0158] Example 8
[0159] This embodiment is substantially the same as Embodiment 1, except that the mass percentage of TiO2 is 4%; the mass percentage of graphene is 7%.
[0160] Comparative Example 6
[0161] This comparative example is substantially the same as Example 1, except that graphene is not included and the mass percentage of titanium dioxide is 9.9%.
[0162] Comparative Example 7
[0163] This comparative example is substantially the same as Example 1, except that titanium dioxide is not included and the mass percentage of graphene is 9.9%.
[0164] Table 1. Performance analysis of materials prepared in comparative examples (D1-D7) and examples (S1-S8)
[0165]
[0166]
[0167] Note: In Table 1, “--” means the elongation is >50 and not broken.
[0168] The high-strength, toughened, lightweight high-entropy alloy nanocomposite material provided by the present invention is prepared by selecting five or more pure metal elements with a purity of not less than 99.95% as raw materials, using a certain mass fraction of two-dimensional sheet materials and nano whiskers as reinforcing agents, and melting them through vacuum arc melting technology. Under a certain vacuum system and in an atmosphere of inert gas argon, the high-strength, toughened, lightweight high-entropy alloy nanocomposite material is obtained after melting for a certain period of time.
[0169] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A lightweight high entropy alloy nanocomposite material, characterized in that: The composite material comprises a light high entropy alloy matrix, whiskers and flaky nanomaterials. Based on the total weight of the composite material, the mass percentage of the whiskers is 0.01wt.% to 5.00wt.%; the mass percentage of the flaky nanomaterials is 0.01wt.% to 10.00wt.%.
2. The material according to claim 1, characterized in that The material of the whiskers includes at least one of MgO, ZnO, Al2O3, BeO, SnO2, MnO2, NiO, Y2O3, CdO, NbO, TiO2, In2O3, GeO2, Cr2O3, TiB2, ZrB2, TaB2, CrB, NbB2, Si3N4, BN, AlN, TiN, SiC, Ni, Fe, Cu, Si, Ag, Ti, mullite, and calcium sulfate.
3. The material according to claim 1, characterized in that The material of the flaky nanomaterial includes at least one of graphene, h-BN, c-BN, MoS2, MoSe2, WS2, hydrotalcite, CuO, WO3, and ZrMo2O8.
4. The material according to any one of claims 1 to 3, characterized in that The whiskers have a length of 1 to 70 μm and a diameter of 0.001 to 0.200 μm; And / or, the particle size of the sheet-like nanomaterial is 10 to 200 nm, and the thickness is 1 to 100 nm.
5. The material according to claim 1, characterized in that The lightweight high entropy alloy matrix includes metal components, and the metal components include at least five of Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Hf, Ta, and W; And / or, the density of the lightweight high entropy alloy is not greater than 7.87 g / cm 3 , preferably 3.5-7.87 g / cm 3 .
6. The material according to claim 5, characterized in that The metal components include a first metal component, a second metal component, a third metal component, a fourth metal component, and a fifth metal component that are different from each other; calculated based on the total atomic percentage of the lightweight high entropy alloy matrix as 100%, the atomic percentages of the first metal component, the second metal component, the third metal component, the fourth metal component, and the fifth metal component are the same or different, and are each independently 5 to 35 at.%.
7. A method for preparing a lightweight high entropy alloy nanocomposite material according to any one of claims 1 to 6, characterized in that: include: A mixture including metal component powders is obtained, subjected to a first vacuum arc melting, and then whiskers and flaky nanomaterials are added and subjected to a second vacuum arc melting to obtain the lightweight high entropy alloy nanocomposite material.
8. The preparation method according to claim 7, characterized in that: The temperature of the first vacuum arc melting is 2500-3000° C., and / or the pressure of the first vacuum arc melting is 0.05-0.08 Pa.
9. The preparation method according to claim 7 or 8, characterized in that: The temperature of the second vacuum arc melting is 1500-1700° C., and / or the pressure of the second vacuum arc melting is 0.05-0.08 Pa.
10. An application of a lightweight high entropy alloy nanocomposite material according to any one of claims 1 to 6 or a lightweight high entropy alloy nanocomposite material prepared by the preparation method according to any one of claims 7 to 9, characterized in that: The lightweight high entropy alloy nanocomposite material is used for parts in the fields of aerospace, medicine, energy, military and transportation.